Multi-Wavelength Q-Switched Ytterbium-Doped Fiber Laser with Multi-Walled Carbon Nanotubes - Al-Masoodi, Ahmed Hasan Hamood; Ahmed, Mahmoud Hazzaa M.; Arof, Hamzah; Harun, Sulaiman Wadi (Taylor & Francis, 2018)
We demonstrate a passively multi-wavelength Q-switched Ytterbium-doped fiber laser (YDFL) based on a multi-wall carbon nanotubes embedded in polyethylene oxide film as saturable absorber. The YDFL generates a stable multi-wavelength with spacing of 1.9 nm as the 980 nm pump power is fixed within 62. 4 mW and 78.0 mW. The repetition rate of the laser is tunable from 10.41 to 29.04 kHz by increasing the pump power from the threshold power of 62.4 mW to 78 mW. At 78 mW pump power, the maximum pulse energy of 38 nJ and the shortest pulse width of 8.87 µs are obtained.